Pengaruh Sponsorship Terhadap Citra Merek Gojek ( Studi Kasus Pada Acara Sepakbola Liga Indonesia Di Kota Padang ) - Heru Aula Azman; Rizky Ramadhanil Hakim (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The aim of the study is to determine the influence of event sponsorship to brand image of Go-jek. sample in this study amuntedto 80 respondents. The criteria in selecting the sample are as follow 1)everyone who use G-jek applicaton, 2) everyone who’s ever watched Liga Indonesia in Padang City. The method that was used inthis study is quantitative method, specifically causal method. the result of the study found that event sponsorhip have significant relationship with brand image.